Serapan Hara dan Peningkatan Produktivitas Jagung dengan Aplikasi Pupuk NPK Majemuk - Kasno, A.; Rostaman, Tia (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2013)
To increase corn yield, an optimum rate of fertilizer is needed. The aims of this study were to study the effect of the NPK compound fertilizer of 15-15-15 on maize yield and to quantify the NPK nutrients uptake. The study was conducted on Inceptisol dryland from December 2011 to April 2012. Completely randomized block design was used consisting of 8 treatments and 3 replications. The fertilizer doses were 0, 50, 100, 200, 300, and 400 kg/ha. Each treatment was added with 250 kg urea/ha. Hybrid corn of Pioneer 12 variety was planted on this experiment. The result showed that both NPK compound and single nutrients fertilizers produced the same yield of maize. The contribution of N nutrient was more pronounced than that of P2O5 or K2O for increasing the maize yield. The highest value of relative agronomic effectiveness was achieved by applying 15-15-15 NPK compound fertilizer at rate of 300 kg/ha plus 250 kg urea/ha. Fertilization of NPK increased the N uptake from 25 to 114 kg/ha, P nutrient from 9 to 51 kg/ha, and K nutrient from 12 to 66 kg/ha, and therefore increased grain yield. P and K nutrient uptake were stored in the grains higher than that in the stover. Uptake of N in the stover was relatively the same as that in the grains.